Retinal oximetry and age-related macular degeneration - Ásbjörg Geirsdóttir 1978- (2015)
Purpose: Neovascular age-related macular degeneration (AMD) is the leading cause of visual impairment and blindness in elderly persons in the industrialised areas. This impairment in vision is caused by pathological neovascularisation and hemorrhages in the fundus with subsequent fibrovascular scar formation. Neovascularisation is generally related to ischaemia and hypoxia, which induces formation of growth factors. One of which is vascular endothelial growth factor (VEGF) but the main treatment of neovascular AMD is with antibodies against VEGF. This, as well as results from other studies, suggests that the retinal oxygen metabolism is disturbed in neovascular AMD. Limited technology has been available to measure oxygenation of the fundus in humans, until recently when our research group developed such apparatus. The aim of the studies in this thesis is to determine if retinal vessel oxygen saturation is abnormal in patients with neovascular AMD. To reach that goal, the retinal oxygen saturation was first measured in healthy persons to standardise the retinal oximetry imaging technique and establish a normal control group. Subsequently, the retinal oxygen saturation was measured in patients with neovascular AMD. Finally, the scope of neovascular AMD and its intravitreal anti-VEGF treatment in Iceland was assessed to evaluate the health-care impact of the disease in Iceland. Methods: The retinal oximetry studies included 120 healthy subjects aged 18-80 years and 46 treatment-naïve neovascular AMD patients aged 66-95 years. The retinal oximeter is based on a fundus camera. With a coupled image splitter it is possible to simultaneously capture two retinal images at two different wavelengths, 570 and 600 nm, with two separate digital cameras. Specialised software calculates the retinal vessel oxygen saturation from the different reflection of light in both arterioles and venules at these two different wavelengths. The population-based AMD incidence study was a prospective study on 439 consecutive patients aged 60 ...